Facile synthesis, and the optical and electrical properties of nanocrystalline ZnFe2O4 thin films. Issue 17 (12th April 2016) - Chakraborty, Mohua; Thangavel, R.; Biswas, Amrita; Udayabhanu, G.
Abstract : Nanostructured zinc ferrite (ZnFe2 O4 ) thin films with uniform grain size distribution have been synthesized using a citrate–nitrate sol–gel and spin coating method. Abstract : Nanostructured zinc ferrite (ZnFe2 O4 ) thin films with uniform grain size distribution have been synthesized using a citrate–nitrate sol–gel and spin coating method. The formation and impact of intrinsic oxygen vacancies in all of the grown samples have been explained with various structural, optical and electrical properties. Low temperature four probe resistivity measurements imply that the conduction mechanism involved impurity and valance band contributions. The high donor density and oxygen vacancies have improved the photocurrent density of the optimized sample from 36.85 to 65.87 mA cm 2 . The optimized sample showed a reduced band gap of 2.316 eV and electrochemical impedance spectroscopy under dark and visible light illumination conditions revealed significantly improved charge transfer properties of the samples. These samples have improved optical absorption and electrical conduction with enhanced photocurrent density and have promise for solar photoelectrochemical applications.